Analisis Zona Rawan Bencana Tanah Longsor Metode Fuzzy Analytical Hierarchy Process (FAHP). Studi Kasus : Daerah Bukit Bual dan Sekitarnya, Kabupaten Sijunjung dan Kota Sawahlunto, Provinsi Sumatera Barat - Borinsky, Arya Danendra; Idarwati (Mataram University, 2025)
Landslides are a significant hydrometeorological threat in Indonesia, particularly in the West Sumatra Province. This research aims to map landslide hazard zones in the Sawahlunto and Tanah Datar regions by integrating the Fuzzy Analytical Hierarchy Process (FAHP) and Geographic Information System (GIS) methods. The FAHP method was utilized to determine the relative weights of four main landslide-inducing parameters: slope, rainfall, land cover, and soil type. Spatial data for each parameter were then analyzed using a weighted overlay technique within the GIS platform to produce a landslide susceptibility map. The FAHP analysis results indicate that slope and rainfall have the most significant influence with weights of 29.86% each, followed by land cover at 29.76%, and soil type at 10.52%, with a consistency ratio (CR) of 0.0006975 signifying a consistent assessment. Based on the spatial analysis, the study area is classified into three susceptibility zones: low, medium, and high. The high-susceptibility zones are generally found in areas with slope gradients >40%, and land cover dominated by rice fields, agricultural fields, plantations, and settlements, despite being characterized by sedimentary soil types and moderate rainfall categories. Conversely, low-susceptibility zones are characterized by gentle slopes (0-2%) and swamp land cover. The findings of this study are expected to provide a scientific basis for local governments in formulating effective disaster mitigation strategies and spatial planning to reduce future risks.